1995
DOI: 10.1038/bjc.1995.379
|View full text |Cite
|
Sign up to set email alerts
|

The response of tumour vasculature to angiotensin II revealed by its systemic and local administration to 'tissue-isolated' tumours

Abstract: Sumnman-A tissue-isolated preparation of the P22 rat carcinosarcoma was used to investigate the tumour vascular response to angiotensin II (ATII). In particular. the relative importance of systemic and local tumour factors was assessed by comparing tumour vascular resistance during systemic administration of ATII and during administration directly into the tumour-supplying artery. The effect of hypervolaemia on tumour vascular resistance was determined as well as the effect of ATII on oxygen metabolism. Tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Both parameters were depressed from normal unanaesthetised values, as expected, and tended to reduce with time, although stabilising towards the end of the procedure. MABP was 72 ± 4 mmHg at the start of the experiment (Figure 7B), which was somewhat lower than we have previously measured in the same animal strain, with propofol 26 or Hypnorm/Hypnovel anaesthesia, 28 as opposed to the isoflurane anaesthesia used here. Consistent with a depressed respiration rate, average arterial oxygen partial pressure (pO 2 ), calculated over the whole experimental time‐course, measured 64 ± 3 mmHg, down from the normal range of 80–100 mmHg.…”
Section: Resultscontrasting
confidence: 58%
“…Both parameters were depressed from normal unanaesthetised values, as expected, and tended to reduce with time, although stabilising towards the end of the procedure. MABP was 72 ± 4 mmHg at the start of the experiment (Figure 7B), which was somewhat lower than we have previously measured in the same animal strain, with propofol 26 or Hypnorm/Hypnovel anaesthesia, 28 as opposed to the isoflurane anaesthesia used here. Consistent with a depressed respiration rate, average arterial oxygen partial pressure (pO 2 ), calculated over the whole experimental time‐course, measured 64 ± 3 mmHg, down from the normal range of 80–100 mmHg.…”
Section: Resultscontrasting
confidence: 58%
“…• donors have been used in vitro to achieve radiosensitisation and cytotoxicity [3,6,7] but their application in vivo at the doses required would result in unacceptable systemic effects [8,9], predominantly hypotension, and so these agents are not ideal for clinical use. Indirect activation of inducible nitric oxide synthase (iNOS), the enzyme responsible for generation of NO…”
Section: Nomentioning
confidence: 99%
“…While the role of NO • in tumours is not fully understood, it is clear from the literature that NO • has enormous potential as an anti-cancer agent if it can be targeted reliably to tumours at high concentrations. Spontaneous and bioreductive NO • donors have been used in vitro to achieve radiosensitisation and cytotoxicity [3,6,7] but their application in vivo at the doses required would result in unacceptable systemic effects [8,9], predominantly hypotension, and so these agents are not ideal for clinical use. Indirect activation of inducible nitric oxide synthase (iNOS), the enzyme responsible for generation of NO • at high concentrations, by interferon gamma (IFNγ ) has also been used in vitro [3], but its systemic toxicity is already well documented [10], and clinical application would be problematical.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced tumor perfusion results in a hypoxic and acidic milieu, which further promotes immunosuppression ( 46 48 ). Vascular endothelial growth factor (VEGF)–induced vascular leakiness ( 48 ) and AngII-mediated vasoconstriction ( 76 , 77 , 80 ) further impair tumor perfusion and aggravate hypoxia. GM-CSF, granulocyte-macrophage colony-stimulating factor.…”
Section: Introductionmentioning
confidence: 99%
“…The impaired perfusion and hypoxic condition of tumors can be further aggravated by AngII-induced vasoconstriction and increased vascular resistance ( Fig. 2 ) ( 76 , 77 ). Our laboratory has shown that AngII transiently enhanced tumor blood flow and interstitial fluid pressure by increasing the mean arterial blood pressure in different tumor types ( 78 , 79 ).…”
Section: Introductionmentioning
confidence: 99%